STUDIES ON PHYSICAL PROPERTIES OF BUKIT KAMANGS’ LIMESTONE AS MINERAL SOURCE FOR LAYING HENS - Khalil, K.; Primasari, B.; Anwar, S. (Journal of the Indonesian Tropical Animal Agriculture, 2011)
Samples of limestone composites were measured for hardness in 5 difference colors: black, darkblue, blue, light blue and white. Limestone was then ground and particle sizes of meal were measured.The meal were mixed with other locally available materials to produce 5 difference mineral formulas:P1: 100% limestone meal, P2: 50% limestone meal + 50% fresh water oyster shell meal, P3: 35%limestone meal + 30% fresh water oyster shell meal + 35% bone meal, P4: 35% limestone meal + 30%fresh water oyster shell meal + 34.2% bone meal + 0.5% salt + 0.3% micro minerals and P5: 100% freshwater oyster shell meal. The formulas were stored for 12 weeks. Samples were taken weekly foranalyzing of moisture content and physical properties. By a feeding trial the five mineral formulas weremixed in the level of 6 % into basal diet and fed to 150 laying hens for 24 weeks. Parameters measuredincluded body weight, feed intake, egg production and FCR. Results showed that the composites ofBukit Kamangs’ limestone had difference hardness. The strongest was found by the black composite of23.4 HRc-C or 245.0 BHN. The meal products contained large particles (>0.42 mm) of 17.8%. Moisturecontent of mineral formulas increased during storage, but their physical properties were no significantchanges. The highest moisture increase was found by the product of 100% limestone, but it could bereduced by mixing with oyster shell meal and bone meal. The best laying performances (P<0.05) werefound by the hens fed with diet supplemented with mineral formula containing limestone, fresh wateroyster shell and fortified with micro minerals.